Women in Medicine Career and Life Management - Bowman, Marjorie A.; Frank, Erica; Allen, Deborah I. (Springer New York, 2002)
In this newly revised, expanded and updated edition, the authors have provided a definitive resource about and for women physicians. From statistical data regarding practicing women physicians in the US and abroad, minorities and gay/lesbian physicians, to practical advice on coping with stress, STRESS AND WOMEN PHYSICIAN is an exceedingly useful and insightful volume for understanding and managing the issues faced by women physicians in both their professional and personal lives